2022
DOI: 10.1111/dsji.12262
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐functional integration skills: Are business schools delivering what organizations need?

Abstract: Practitioner surveys suggest that despite well-intentioned efforts, undergraduate business programs could better equip students with "soft skills." This research study focuses on the soft skills associated with cross-functional integration (CFI), where skill gaps are believed to exist but have not been confirmed. As the first study to specifically characterize and measure CFI skills, we argue that even in the best-case scenario, a small CFI-skills gap could persist, and that the primary goal of business progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…The data shows a positive environment for CFI in managing processes, with efforts towards synchronization and mutual understanding of the larger process among different functional units. The above finding aligns with the work of Souza et al (2022), which underscores the pivotal role of CFI in coordination. Souza et al's (2022) study aligned with the present study's findings on the significance attached to the synchronization of functional activities, as evidenced by the high rating in the table.…”
Section: Coordinationsupporting
confidence: 86%
See 1 more Smart Citation
“…The data shows a positive environment for CFI in managing processes, with efforts towards synchronization and mutual understanding of the larger process among different functional units. The above finding aligns with the work of Souza et al (2022), which underscores the pivotal role of CFI in coordination. Souza et al's (2022) study aligned with the present study's findings on the significance attached to the synchronization of functional activities, as evidenced by the high rating in the table.…”
Section: Coordinationsupporting
confidence: 86%
“…Souza et al's (2022) study aligned with the present study's findings on the significance attached to the synchronization of functional activities, as evidenced by the high rating in the table. Souza et al (2022) found that organizations that highly value CFI skills have recognized coordination as a critical factor in achieving success. This coincides with the present study's positive environment for CFI, emphasizing the need for organizations to prioritize and enhance coordination skills across functions.…”
Section: Coordinationmentioning
confidence: 99%
“…In this way, given the existence of differences in the needs for certain skills, teachers would have to complement this more homogeneous higher education with other more specific training in order to achieve a better future link between company-university at a national level. In agreement with other authors, this paper emphasises that it is crucial that there be regular communication between companies and training centres and that representatives of the tourism industry participate in the process (Regalado Pez ua and Montoya, 2012;Blesia et al, 2021;D'Souza et al, 2022). Curricula and delivery methods should be updated, upgraded and refreshed to address the new industry skills and requirements (Sigala, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…When educational programmes respond to the needs of industry, the university can gain a competitive advantage (Lo, 2005). Therefore, some authors suggest the need for coordination and regular communication between business and training centres, thus improving the competitiveness of companies and reducing the gap that currently exists (Blesia et al, 2021;D'Souza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…-Universities to develop a greater entrepreneurial awareness (Nicolaides, 2011; African Union, 2020). -universities must develop cross-functional thinkers who are innovative and have entrepreneurial skills that are needed in the local economy (Clark et al, 2004;D'Souza et al, 2022). -Universities to encourage entrepreneurship by making use of innovative programme designs and specialist post-graduate programmes in entrepreneurship, with explicit academic entrepreneurship bias (Wadee and Padayachee, 2017).…”
Section: Promotion Of Entrepreneurshipmentioning
confidence: 99%